A tree-based data collection protocol for optical unmanned aerial vehicle networks. (February 2018) - Ramdhan, Nihel; Sliti, Maha; Boudriga, Noureddine
Abstract: In Wireless Sensor Networks (WSNs), sensors are spread over a remote and hardly accessed sensing zone. In this situation, Unmanned Aerial Vehicles (UAVs) allow to facilitate the data gathering from sensors in real time. In the present paper, we consider an optical UAV network that allows the real time data distribution to a base station, based on multiple collection trees and multiple base stations. Each UAV is identified by an optical codeword with adequate structure to reduce the codeword management process implied by the UAV mobility. Using the attributed codewords, each UAV can optically switch the gathered data to reach a base station for processing. Furthermore, we present quality-based attachment and re-attachment procedures allowing to an UAV to attach and re-attach to a tree whether it notices the quality degradation of its link to the collection tree.